Profil Tingkah LakuAgresi Peserta Didik Di SMP Negeri 31 Padang - Fadillah, Annisa Citra; Ibrahim, Indra; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
This research was based on violence phenomenon that happened among the student whether in verbally or physically in school environtment. Verbal violence that happened in school was abaout the studentâs embrassed, humiliated and octracized by the other student. Meanwhile, physical violence that occurs in school was hitting, pulling, and fighting with the other studentâs. This study was descriptive qualitative research. Population of this research was all of thestudent of SMP N 31 Padang that consisted of 772 studentâs. This research used Stratified Random Sampling as sampling technique. The amount of sample were 88 studentâs. The instrument that used in this research was questionnaire. Meanwhile, the research analyzed the data by using prensetation technique. Verbal behavior aggression stated in chategory of many with presentageÂ was 59,09% and studentâs physical behavior aggression stated in chategory many with presentage 70,45%.